1994
DOI: 10.1515/labm.1994.18.2.62
|View full text |Cite
|
Sign up to set email alerts
|

Verlauf von zirkulierendem Fibrinogen beim akuten Myokardinfarkt unter thrombolytischer Therapie mit rt-PA

Abstract: In 12 patients treated with WO mg rt-PA 3 h for acute myocardial infarction (AMI), serial fibrinogen levels were measured with the Clauss clotting rate assay ("functional 62Lab.med. 18: 62 (1994) Brought to you by | University of Queensland -UQ Library Authenticated Download Date | 6/18/15 8:57 PM Originalie J fibrinogen ") andwith a newenzyme immunoassay for immunologically intact fibrinogen ("intact fibrinogen "). Levels off u national and intact fibrinogen were strikingly different: fuYictional levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Other routine fibrinogen assays include the prothrombin time‐derived assay (PTF) [14]; and the immunonephelometric assay [15]. When the ratio of values found with the von Clauss assay and those obtained using a recently developed ELISA for the total of high molecular weight (HMW) and low molecular weight (LMW) fibrinogen (intact fibrinogen, ITF) was calculated, normal donors had a ratio close to 1, whereas patients with acute MI had a mean ratio of 1.6 before thrombolytic therapy, rising to 2.1 at 24–72 h after therapy [16–19]. It was suggested that this increased ratio represents ‘hyperfunctional’ fibrinogen (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Other routine fibrinogen assays include the prothrombin time‐derived assay (PTF) [14]; and the immunonephelometric assay [15]. When the ratio of values found with the von Clauss assay and those obtained using a recently developed ELISA for the total of high molecular weight (HMW) and low molecular weight (LMW) fibrinogen (intact fibrinogen, ITF) was calculated, normal donors had a ratio close to 1, whereas patients with acute MI had a mean ratio of 1.6 before thrombolytic therapy, rising to 2.1 at 24–72 h after therapy [16–19]. It was suggested that this increased ratio represents ‘hyperfunctional’ fibrinogen (i.e.…”
Section: Introductionmentioning
confidence: 99%